Enhancing embedded systems simulation a chip-hardware-in-the-loop simulation framework (Vieweg+Teubner, 2011)
Using the real Microcontroller (µC) as a replacement for a µC model inside a system simulation of a µC-based system is a big benefit since the µC is already verified. Moreover, its maximum performance and its accuracy are much higher than any simulation model. With the Chip-Hardware-in-the-Loop Simulation (CHILS) approach, Christian Köhler covers the connection between µC and simulation, the analysis and optimization of such coupling systems as well as the interface abstraction. He develops the hardware to simulation coupling system with a focus on less hardware effort, the capabilities to couple with different simulation environments, and the efficiency of coupling. The interface abstraction primarily supports the efficiency of coupling. The system analysis and optimization concepts include formal criteria to determine the fidelity of Hardware-in-the-Loop (HIL) coupling systems, stability analysis of coupling systems, and the numerical analysis of applied software algorithms. Furthermore, the author presents existing concepts to simulate complex systems and compares them with the new app